1989
DOI: 10.1084/jem.170.4.1149
|View full text |Cite
|
Sign up to set email alerts
|

Infection of monocyte-derived macrophages with human immunodeficiency virus type 1 (HIV-1). Monocyte-tropic and lymphocyte-tropic strains of HIV-1 show distinctive patterns of replication in a panel of cell types.

Abstract: To characterize the host range of different strains of HIV-1, we have used four types of cells, primary monocyte-derived macrophages (MDM), primary PBL, a promonocyte cell line (U937), and a CD4+ T cell line (SUP-T1). These cells were infected with three prototype strains of HIV-1, a putative lymphocyte-tropic strain (IIIB), and two putative monocyte-tropic strains (SF162 and DV). Infections were monitored by assays for infectious virus, for cell-free and cell-associated viral antigen (p24), and for the propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(84 citation statements)
references
References 50 publications
3
81
0
Order By: Relevance
“…We also reported that passive transfer of anti-V3 MAb KD-247 successfully suppressed HIV-1 viral load in vivo (16). Given the recent studies showing that anti-V3 antibodies exert immune pressure on circulating and transmitted viruses and may play a role in reducing the infection rate in both adults and infants born to infected mothers, strategies based on 0.5g scFv or other anti-V3 antibodies could be particularly effective (7,11,19,29,39). In addition, combination of 0.5g scFv with certain CD4-mimetic compounds may deserve further investigation as the combination of KD-247 with certain CD4-mimetics markedly enhances the neutralization/binding activity in vitro (40).…”
Section: Discussionmentioning
confidence: 99%
“…We also reported that passive transfer of anti-V3 MAb KD-247 successfully suppressed HIV-1 viral load in vivo (16). Given the recent studies showing that anti-V3 antibodies exert immune pressure on circulating and transmitted viruses and may play a role in reducing the infection rate in both adults and infants born to infected mothers, strategies based on 0.5g scFv or other anti-V3 antibodies could be particularly effective (7,11,19,29,39). In addition, combination of 0.5g scFv with certain CD4-mimetic compounds may deserve further investigation as the combination of KD-247 with certain CD4-mimetics markedly enhances the neutralization/binding activity in vitro (40).…”
Section: Discussionmentioning
confidence: 99%
“…contrast, expression of CCR5, the major coreceptor for macrophage-tropic strains of HIV-1, remained unchanged and, in some donors, was even up-regulated on the surface of M2a MDM vs M1 and controls. CXCR4, an entry coreceptor for X4-dependent viruses (which do not usually cause productive infection in MDM) (46,47), was also down-regulated in polarized MDM vs controls (Table I).…”
Section: M1 and M2a Polarization Differentially Modulates The Expressmentioning
confidence: 96%
“…Within a short time, they migrate into various tissues and mature into macrophages. These mononuclear cells also have the ability to cross the blood-brain barrier (BBB) and to enter the central nervous system (CNS), where they act as an important target and reservoir of HIV-1 [17][18][19][20][21]. HIV-1-infection of the brain can lead to HIV dementia, a primary disorder of the CNS, which affects nearly 25% of untreated, HIV-1-infected individuals [22].…”
Section: Introductionmentioning
confidence: 99%